European History in the Shadows of Crisis. (17th October 2022) - Mercer, Ben; Pattison, Micaela
Abstract: This article situates the practice of history in the commemoration and experience of contemporary crises. It argues that the current preoccupation with crisis reflects a failure of historical imagination produced by short‐term thinking that increasingly also governs higher education. The concept of crisis often falls short as a tool for understanding both the past and the contemporary world. Histories and accounts that emphasise sudden crisis or triumphal narratives of resolution fail to account for the deep structures and long‐term struggles that can be illuminated by historical research.